Pembatasan Masa Jabatan Presiden dalam Rangka Mewujudkan Negara Hukum Demokratis - Gusman, Delfina Gusman; Syofyan, Yunita Syofyan (Jurnal Legislasi Indonesia, 2023)
Indonesia as rule of law by characteristic republic and presidential system. Article of 1 paragraft 2 regulation of 1945 so “sovereignty in the handful of society and implementation according of regulation of 1945". The definition of Sovereignty is about exsistension society of law, society have the constitutional rights against election regional chief and especially president as country leader. General election (Pemilu) is democracy instrument for society for right to vote to president as leader for country. Article 22 E paragrafh 1 regulation of 1945 so “general election implement by direct, general,freedom, impartial, honest, and fair every once five year. In this last three years,have planning to amendment a regulation of 1945 because of some factor politic dinamica growth until now. The result of research tell so the regulation of president in Indonesia purpose to avoid for the action of otoritary by the position  as president and also give a opportunity next candidate as president for placement in the position as president of Indonesia according democracy philosophy. Accordibg article of 7 regulation of 1945 still have weakness against term of position as president so that need some new idea as solution from weakness of regulation about term of position president in the future (ius constituendum) become solution against the weakness. And then, the limits of power by legal basic have to implement by constitutional agreement especially convention. Therefore the legal problem in above so the ideal regulation against president and vice president by legal product especially regulations or convention but must be refer to Article of 7 Regulation of 1945